Image-based multilevel biomechanical modeling for fall-induced hip fracture - Luo, Yunhua (Springer, 2017)
Fall-induced hip fracture is an epidemic health risk among elderly people. This book presents an image-based multilevel modeling approach to understanding the biomechanics involved in fall-induced hip fracture. By hierarchically integrating a body-level dynamics model, a femur-level finite element model, and a local bone failure model, the biomechanics approach is able to simulate all stages in sideways falls and to incorporate all biomechanical variables affecting hip fracture. This book is useful for clinicians to accurately evaluate fracture risk, for biomechanical engineers to virtually test hip protective devices, and for biomedical students to learn image-based biomechanical modeling techniques. This book also covers: Biomechanical viewing on bone composition, bone remodeling, and bone strength Bone imaging and information captured for constructing biomechanical models Bone mechanical testing and mechanical properties required for biomechanical modeling.
Keywords: Hip joint -- Fractures -- Mathematical models.; Biomechanics -- Simulation methods.; elektronické knihy; electronic books